Validating the Measurement of Maqasid Syariah Quality of Life (I-QoL) Model among Spiritual Rehabilation Drug Abusers - Mahadzirah, Mohamad; Nizaita, Omar; Nor Azman, Mat Ali @ Salim; Harmy, Mohamed Yusoff (2015)
The purpose of this study is to validate the proposed measurement model of Maqasid Syariah quality of life among drug abusers who are getting spiritual rehabilitation treatments. The proposed model consists of five elements of Maqasid Syariah which comprised of religion, life, mind, lineage and property. The main objective of the study is to ascertain items (observed variables) that operationalised latent components of Maqasid Syariah quality of life. The study was conducted at several drug rehabilitation centres in Terengganu. A total of 196 respondents involved in the study. Respondents were asked to give their responses using self-administered questionnaires guided by trained enumerators. The reliability and validity of the measurement model was tested using structural equation modelling (SEM) using AMOS 21. The cleaned data was subjected to several statistical analyses such as exploratory and confirmatory factor analysis, reliability, convergent and discriminant validity. The findings of the study suggested that the construct of Maqasid Syariah quality of life, Religion was measured by sixteen items. Both Life and Lineage were measured by twelve observable items. Mind and Property were measured by nine and seven observable items respectively.